Upholding the fundamental values of infection prevention and antimicrobial stewardship in the current political climate - Priya Nori; Gonzalo Bearman (Antimicrobial Stewardship & Healthcare Epidemiology)
The healthcare and public health communities must adjust to a series of damaging, anti-science, and anti-innovation policies of the new administration. After a brief review of new healthcare and public health-oriented federal policies, we outline priority areas for the infection prevention and antimicrobial stewardship workforce and offer solutions for adaptation.